2016
DOI: 10.1186/s12284-016-0135-0
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping of Grain Quality Traits Using Introgression Lines Carrying Oryza rufipogon Chromosome Segments in Japonica Rice

Abstract: BackgroundImproved eating quality is a major breeding target in japonica rice due to market demand. Consequently, quantitative trait loci (QTL) for glossiness of cooked rice and amylose content associated with eating quality have received much research focus because of their importance in rice quality.ResultsIn this study, QTL associated with 12 grain quality traits were identified using 96 introgression lines (IL) of rice developed from an interspecific cross between the Korean elite O. sativa japonica cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 41 publications
(90 reference statements)
2
36
0
Order By: Relevance
“…In the present study, replacement of the ZS97 allele of RFT1 with the MY46 and ZH11 alleles resulted in increasing the contents of most amino acids ( Supplementary Table S2; Tables 3-5). Obviously, the effects of RFT1 on HD and AAC have opposite allelic directions, which is in accordance with the opposite allelic directions between QTLs for HD and PC located on the short arm of chromosome 6 (Wada et al, 2006;Yun et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the present study, replacement of the ZS97 allele of RFT1 with the MY46 and ZH11 alleles resulted in increasing the contents of most amino acids ( Supplementary Table S2; Tables 3-5). Obviously, the effects of RFT1 on HD and AAC have opposite allelic directions, which is in accordance with the opposite allelic directions between QTLs for HD and PC located on the short arm of chromosome 6 (Wada et al, 2006;Yun et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
“…Utilization of the pleiotropic effects of heading-date genes on AAC and PC could help to meet the diverse requirements of protein for human consumption. High contents of protein and amino acids are favorable for enhancing the nutritional value, but unfavorable for eating quality (Martin and Fitzgerald, 2002;Kwon et al, 2011;Yun et al, 2016) and undesirable for some uses such as wine-making (Yoshida et al, 2002) and certain types of diet . Alleles for promoting HD and increasing AAC could be selected for developing rice varieties with high nutritional values; and alleles for delaying heading and reducing AAC may be applied for developing high-yielding varieties with good eating quality.…”
Section: Xie Et Al Rft1 Affecting Amino Acid Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer and utilization useful genes from wild rice into cultivated varieties are effective and aim to improve grain yield, quality, and crop genetic diversity (Brar and Khush 1997;Xie et al 2008;Yun et al 2016;Qi et al 2017). However, efforts to improve rice grain traits of modern cultivars using O. minuta as donor parents are limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, low crossability and limited recombination between unrelated genomes limit the transfer QTLs from Oryza minuta to cultivars. Following the availability of advanced backcross quantitative trait loci (AB-QTL) approach proposed by Tanksley and Nelson (1996), several studies have been reported to identify the QTLs controlling yield and quality-related traits and to simultaneously transfer them from wild to cultivated species (Xiao et al 1998;Thomson et al 2003;Yoon et al 2006;Tian et al 2006;Mallikarjuna Swamy et al 2012;Yun et al 2016). However, few attempts have been made to identify and capture yield-related QTLs from Oryza minuta into cultivars.…”
Section: Introductionmentioning
confidence: 99%